Primary Leiomyosarcoma in the Inferior Vena Cava Extended to the Right Atrium: A Case Report and Review of the Literature - Fujita, Shuichi (Case Rep Oncol, 2016)
A 38-year-old woman had developed an abdominal distention, lower extremity edema, and dyspnea. Imaging examination revealed a large mass in the right atrium which was connected to lesions within the inferior vena cava. Although complete resection of the mass was not possible, partial surgical tumor resection was performed to avoid pulmonary embolization and circulatory collapse. Leiomyosarcoma was diagnosed histologically, and chemotherapy (doxorubicin) followed by radiotherapy was started. By reviewing papers published in the past 10 years that included 322 patients, we also discuss the clinical presentations and prognosis of leiomyosarcoma in the inferior vena cava.